FINITE ELEMENT ANALYSIS OF LAW OF THERMO MECHANICAL COUPLING DEFORMATION AND DYNAMIC CHARACTERISTICS OF RAIL BEAM OF TRUSS PIPE PULLING ROBOT - LI ZhenJie; LI DongShuai; SONG Yan (Jixie qiangdu)
The truss-type pipe-pulling robot serving the large centrifugal pipe casting machine has important influence on the accuracy due to its large travel and heavy load. By using finite element method,the thermo-mechanical coupling static deformation law of long-span X-direction beam was analyzed and the structure was optimized. The static deformation law and dynamic time-domain response of Y-direction beam were analyzed. The results show that the thermal-mechanical coupling deformation of the optimized X-direction beam is about 0. 15 mm,which is 3% of the original scheme; The deformation of Ydirection beam is about 0. 67 mm,its dynamic response converges,the transition time is short,and the vibration times are about1. 5. The analysis results show that the static characteristics and dynamic response of the robot can meet the engineering needs.The engineering application was carried out,and the practical results are in good agreement with the finite element analysis. The conclusion is of great significance to casting automation of centrifugal casting pipe.